Genomics applied to the study of adaptation in pine species - Guevara, M.A.=700 1 Soto, A.; Collada, C.; Plomion, C.; Savolainen, O.; Neale, D.B.; Gonzalez Martinez, S.C.; Cervera, M.T.
(Es, En)
ilus., 109 ref.
Keywords: PINUS; GENOMAS; GENES; MAPAS GENETICOS; ESPAÑA; MAPEO DE ASOCIACION